(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2025)
This piece highlights the accomplishments of two prolific writers of the 20th century, Jorge Luis Borges and Saint John Perse. This essay compares the style and themes of both authors, arguing that Borges, like Perse, deserved the Nobel prize for effectively conveying concepts of metaphysics—such as time, emotion, and knowledge—with a similarly abstract approach. For additional context, listen to the author’s reflection on the piece below.